2018
DOI: 10.1007/s00125-018-4740-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of an integrated primary–secondary model of care for individuals with complex type 2 diabetes: a non-inferiority randomised controlled trial

Abstract: Aims/hypothesis The aim of the study was to determine if a Beacon model of integrated care utilising general practitioners (GPs) with special interests could achieve similar clinical outcomes to a hospital-based specialist diabetes outpatient clinic. Methods This pragmatic non-inferiority multisite randomised controlled trial assigned individuals with complex type 2 diabetes to care delivered by a Beacon clinic or to usual care delivered by a hospital outpatient department, in a 3:1 ratio. Owing to the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…Although we used simple pragmatic questionnaires to assess participant satisfaction, there were marked increases in the proportions of participants moderately or very satisfied with key aspects of diabetes management as a result of DCCC involvement. This finding parallels that in the Beacon randomised trial in which scores on a validated client satisfaction questionnaire were higher in participants in the Beacon programme compared to those in usual outpatient clinic care 7 . It is possible that the relatively high satisfaction rate in the DCCC was a major factor underlying the low non‐attendance rate for scheduled appointments.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Although we used simple pragmatic questionnaires to assess participant satisfaction, there were marked increases in the proportions of participants moderately or very satisfied with key aspects of diabetes management as a result of DCCC involvement. This finding parallels that in the Beacon randomised trial in which scores on a validated client satisfaction questionnaire were higher in participants in the Beacon programme compared to those in usual outpatient clinic care 7 . It is possible that the relatively high satisfaction rate in the DCCC was a major factor underlying the low non‐attendance rate for scheduled appointments.…”
Section: Discussionsupporting
confidence: 69%
“…In the two Brisbane Beacon studies reported to date, there were similar average falls in HbA 1c of 1.1% 6 and 1.3% 7 (12 and 14 mmol/mol respectively) at 6 months, and 0.8% 6 and 1.1% 7 (10 and 12 mmol/mol respectively) at 12 months, from a similar baseline HbA 1c (8.6% 6 and 9.4%, 7 or 70 and 79 mmol/mol, respectively, compared to 9.4% or 79 mmol/mol in the present study). Although we did not have a comparator group, the most recent Beacon trial included a usual hospital outpatient care arm and the Beacon model proved non‐inferior for glycaemic efficacy 7 . This suggests that DCCC participants were not disadvantaged by utilising integrated care in the community rather than specialist clinics.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations